PENGEMBANGAN MODEL ADMINISTRASI PEMBELAJARAN TERPADU 360 BERBASIS GOOGLE SITES YANG ADAPTIF DAN REPLIKATIF UNTUK GURU SD/MI (STUDI PENGEMBANGAN PADA KELAS III MI AL IKHLAS PARAKAN KAUMAN) - Yoga Dwi Prada; Azamul Fadhly Noor Muhammad; Laili Maulida Ali (Jurnal Manajemen Pendidikan, 2026)
This study aims to develop an adaptive and replicable digital learning administration model, namely TERPADU 360 based on Google Sites, to improve the efficiency of administrative management among elementary school teachers. The development of this model is motivated by the low level of integration in learning administration systems at the elementary school level, which affects the effectiveness of teachers’ work. This research employs a Research and Development (R&D) method using the 4D development model (Define, Design, Develop, Disseminate). The research subjects were third-grade teachers at MI Al Ikhlas Parakan Kauman, selected using purposive sampling techniques. Data were collected through expert validation, teacher response questionnaires, and system usage observations. The results indicate that the developed model has a high level of feasibility, with a practitioner validation score of 93.84%, and material and media expert validation scores of 92.30%, both categorized as feasible with revisions. The novelty of this research lies in the development of a Google Sites based learning administration model that is adaptive and replicable, enabling it to be easily implemented and replicated by elementary school teachers in various educational contexts.